Educação continuada baseada em aprendizagem independente (proativo): experiência da Revista Brasileira de Cirurgia Cardiovascular - Souza, Eliana Pereira Salles de (2013)
Continuing Online Medical Education has been considerably enhanced by the improvement of technology. This provided the update and dissemination of science studies directed related to the health professional in a sensitive and effective way due to both fast transmissions of information and easy and unlimited access of content from virtually anywhere. The aim of this study was to describe the process of building up a system of Continuing Online Medical Education based on scientific articles published in the Brazilian Journal of Cardiovascular Surgery (BJCVS). ll the process of developing and visualizing the system on the user's computer is described. The study showed that the system of Continuing Online Medical Education designed by BJCVS is viable. It is also a fast, free, easy, and updated way to improve professional knowledge by using groundbreaking technology resources and examining carefully the information in the area with recent publications.